Seven functional classes of Barth syndrome mutation - Whited, Kevin (Oxford University Press, 2013)
Patients with Barth syndrome (BTHS), a rare X-linked disease, suffer from skeletal and cardiomyopathy and bouts of cyclic neutropenia. The causative gene encodes tafazzin, a transacylase, which is the major determinant of the final acyl chain composition of the mitochondrial-specific phospholipid, CL. In addition to numerous frame shift and splice-site mutations, 36 missense mutations have been associated with BTHS. Previously, we established a BTHS-mutant panel in the yeast Saccharomyces cerevisiae that successfully models 18/21 conserved pathogenic missense mutations and defined the loss-of-function mechanism associated with a subset of the mutant tafazzins. Here, we report the biochemical and cell biological characterization of the rest of the yeast BTHS-mutant panel and in so doing identify three additional modes of tafazzin dysfunction. The largest group of mutant tafazzins is catalytically null, two mutants encode hypomorphic alleles, and another two mutants are temperature sensitive. Additionally, we have expanded the defects associated with previously characterized matrix-mislocalized-mutant tafazzins to include the rapid degradation of aggregation-prone polypeptides that correctly localize to the mitochondrial IMS. In sum, our in-depth characterization of the yeast BTHS-mutant panel has identified seven functional classes of BTHS mutation.